Does an Islamic label indicate good corporate governance? - Hayat, Raphie; Kabir Hassan, M. (Journal of Corporate Finance, 2017)
In this paper we study the effect of an Islamic label on corporate governance. Listed firms with an Islamic label (Islamic firms) are characterized by low leverage. Because recent evidence indicates that leverage can act as a substitute for good governance, it is tempting to expect these Islamic firms to have better governance than their non-Islamic peers. However, we find no significant difference in overall governance between Islamic and non-Islamic S&P 500 firms. Also, after controlling for other determinants of governance, we find no significant effect of an Islamic label. We do find that an Islamic label adds about 2 percentage points of governance quality, as measured by the Bloomberg Governance Disclosure score. However, this effect is not related to leverage.